Analisis Tax Avoidance Berdasarkan Faktor Internal Perusahaan Dengan Tata Kelola Komisaris Independen Sebagai Variabel Moderasi - Regas, Roshan; Hardiningsih, Pancawati (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2025)
Tax avoidance is a company's effort to reduce the tax burden that must be paid legally, without violating applicable tax regulations. This strategy is carried out by utilising certain loopholes or provisions in the tax system, so that the amount of tax payable can be reduced and the company's net profit can be optimised to support its business continuity. This study aims to evaluate and examine the effect of capital intensity and profitability on tax avoidance practices, with the presence of independent commissioners as a variable that moderates the relationship. The research focuses on manufacturing companies engaged in the consumer non-cyclicals sector and listed on the Indonesia Stock Exchange (IDX), specifically in the cosmetics and household goods sub-sector and the food and beverage sub-sector, during the period 2021 to 2024. From a total of 111 companies in the sector, the sample determination was carried out through a purposive sampling method, which resulted in 17 companies that met the criteria. With a time span of 4 years, the total observation data used in the analysis is 68. The analysis research shows that capital intensity and firm size have a positive but insignificant effect on tax avoidance. In contrast, profitability has a significant negative effect on tax avoidance. Meanwhile, independent commissioners are unable to moderate the relationship between profitability and tax avoidance significantly. The leverage variable was found to have no effect on tax avoidance.